Mechanical properties of ambient cured high-strength plain and hybrid fiber reinforced geopolymer composites from triaxial compressive tests - Khan, Musaad Zaheer Nazir; Hao, Y.; Hao, Hong; Shaikh, Faiz Uddin Ahmed; Liu, K. (Elsevier BV, 2018)
Geopolymer binders have evolved as a promising alternative to ordinary Portland cement (OPC) in concrete over the last few decades. However, many aspects of their mechanical behaviour such as their performance under multiaxial stress conditions are still unknown, which are of primary importance for their structural application. In this paper, the triaxial compressive behaviour of newly developed ambient-cured high-strength geopolymer (HSG) mortar, and fiber reinforced geopolymer composites (FRGC) is studied. A series of Ø50 × 100 mm cylindrical samples were prepared using low-calcium fly ash and ground granulated blast furnace slag, while hybrid steel-polyethylene fiber reinforcement with fiber volume fraction of 2% was used to reinforce the brittle geopolymer matrix. Standard triaxial tests with fifteen different levels of confining pressures [(s3); ranging between 0 and 100 MPa] were employed to comprehensively investigate the triaxial stress-strain characteristics of synthesized materials from low to high range of confining pressures. According to test results, the unreinforced HSG samples exhibited linear elastic stress-strain behaviour under uniaxial stress condition and showed catastrophic brittle failure. Instead, the samples tested under confinement showed pseudo-ductile behaviour. On the other hand, the inclusion of hybrid-fiber reinforcement has meaningfully helped to improve the ductility of HSG matrix. The peak axial stress and the corresponding axial strain was found to increase with the increase of confining pressure, although the influence of active lateral confinement was more pronounced on the triaxial strength of HSG samples. The two most commonly used failure criterions for OPC concrete, i.e., Power-law and Willam-Warnke failure criterion were used to develop the empirical relations to predict the peak axial stress as a function of confining pressure for the studied materials. The proposed relationships can be used for the calibration of existing concrete material models. The obtained test results were also compared with the existing triaxial compression test data on high strength cement based concretes and composites in the literature to highlight the differences between geopolymers and OPC concrete.